The disruptions and the opportunities in FinTech / Ilham Adli Azahar. - Azahar, Ilham Adli (2019)
A study of the disruptions and the opportunities in FinTech. The design of this study is using qualititative method. Library research has been used for this research. The data collection methodology used in this research is deductive method. Based on the previous researches and findings, there are many disruptions happened to the financial institution in the FinTech development. Despite all the challenges, FinTech brings more opportunities to the financial consumers and financial institutions. It is because FinTech is more relevant and convenient to all the economic units, and it is competent to be implemented in the financial world.